MENTAL HEALTH DISORDERS IN INDONESIA: Impact and Urgency Based on the Perspective of Psychology and Islamic Sociology - Gustiani, Indah (UIN Sunan Kalijaga Yogyakarta, 2023)
Mental health disorders are processes in which individuals are unable to recognize and satisfy their needs. Mental health disorders are prevalent in society and have a major impact on individuals and communities. This abstract provides an overview of various mental health disorders in the wider community. The methodology used is to conduct a literature review using a systematic search in books and electronic journals published until January 2023. The results show that there is a mistake in treating sufferers of mental health disorders in Indonesia. People with mental disorders are considered dangerous so that many people avoid and even isolate sufferers. The conclusion of this article is an explanation of the main impact and urgency to overcome the problems of mental health disorders that occur in society based on the views of the Psychology and Islamic Sosiology. Keywords: Mental Health Disorders, Psychology, Islamic Sociology